2020
DOI: 10.1016/j.future.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Predicting likelihood of legitimate data loss in email DLP

Abstract: The volume and variety of data collected for modern organizations has increased significantly over the last decade necessitating the detection and prevention of disclosure of sensitive data. Data loss prevention is an embedded process used to protect against disclosure of sensitive data to external uncontrolled environments. A typical Data Loss Prevention (DLP) system uses custom policies to identify and prevent accidental and malicious data leakage producing large number of security alerts including significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The article describes the implemented software complex consisting of secure corporate chat and DLP-system in the form of security monitor; defines the functional requirements, and performs the algorithmic and the software design [15]. Its advantages include speed performance, effectiveness, simplicity of using, controlling of the employees correspondence with the search of forbidden words and phrases in the dictionaries; the sufficient minimal functionality for tracking the events on the system and detecting the threats, the prevention of the information leakage; and low cost software [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The article describes the implemented software complex consisting of secure corporate chat and DLP-system in the form of security monitor; defines the functional requirements, and performs the algorithmic and the software design [15]. Its advantages include speed performance, effectiveness, simplicity of using, controlling of the employees correspondence with the search of forbidden words and phrases in the dictionaries; the sufficient minimal functionality for tracking the events on the system and detecting the threats, the prevention of the information leakage; and low cost software [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…In the process of data collection, due to the influence of various factors, data loss may occur, resulting in incomplete or discontinuous data and affecting data analysis [12].…”
Section: Indicator Selection and Data Collectionmentioning
confidence: 99%
“…Of course, articles describing this approach (Faiz et al, 2020), where an e-mail attachment is just seen as a yes or no flag, have been shown to have some scientific backing. On top of this, well defined and barely changing processes can be protected against many cases of data leakage using this method, so it is predestined to be used in high-security environment.…”
Section: Data Leakage Preventionmentioning
confidence: 99%